CERVICAL PREGNANCY: DIFFERENT CLINICAL SCENARIOS LEADING TO ITS DIAGNOSIS - Galvão, Ana (2017)
We report all the cases of cervical pregnancy managed in our institution in the past ten years. One of them was treated with methotrexate. The other one was the result of in vitro fertilization, leading to an early embryo reduction. The last one was misdiagnosed as an uterine abortion and was submitted to dilatation and curettage with profuse bleeding, uterine perforation and need of laparotomy. As it continues to be a rare condition, the most important step in cervical pregnancy continues to be thinking about the possibility of its occurrence, because if it remains unrecognized it may have an end in an unfavorable outcome.